Ion-implanted deuterium release behavior from Li-based advanced ceramics - Tolstolutskaya, G.D.; Karpov, S.A.; Ruzhytskiy, V.V.; Nikitin, A.V. (Problems of Atomic Science and Technology, 2022)
The behavior of ion-implanted deuterium in advanced lithium orthosilicate (Li₄SiO₄) pellets with addition of lithium metatitanate (Li₂TiO₃), and in reference Li₄SiO₄ pellets, has been studied. Thermal desorption spectroscopy (TDS) was used to examine the deuterium interaction with radiation defects in materials. Deuterium gas release from studied ceramics has revealed a clear dependence of deuterium trapping behavior on phase composition. The trap strength of radiation defects formed in lithium titanate was found to be higher than in lithium orthosilicate. Досліджено поведінку іонно-імплантованого дейтерію в удосконалених таблетках ортосилікату літію (Li₄SiO₄) з додаванням метатитанату літію (Li₂TiO₃) та в еталонних таблетках Li₄SiO₄. Для вивчення взаємодії дейтерію з радіаційними дефектами в матеріалах використовувалася термодесорбційна спектроскопія (ТДС). Виділення дейтерію з досліджуваних керамік виявило чітку залежність характеру захоплення дейтерію від фазового складу. Було встановлено, що енергія зв'язку дейтерію з радіаційними дефектами в титанаті літію вища, ніж у ортосилікаті літію.